P117 Serum proteomic analysis characterises newly diagnosed Crohn's disease and ulcerative colitis depending on the age at diagnosis. (16th January 2018) - Verstockt, S; Glorieus, E; De Decker, M; Verstockt, B; Ardeshir Davani, N; Ballet, V; Van Assche, G; Hindryckx, P; Ferrante, M; Laukens, D; Mana, F; De Vos, M; et al.
Abstract: Background: Inflammatory bowel disease (IBD) is characterised by a chronic inflammation of the gut with a poorly understood ethiopathogenesis. Clinical phenotypes are heterogeneous, partly depending on age at diagnosis. To get a better understanding of underlying mechanisms at the time of diagnosis, and possible age-related differences, we studied the inflammatory serum protein profiles of patients newly diagnosed with Crohn's disease (CD) or ulcerative colitis (UC), naïve for biologicals and immunosuppressives. Methods: We prospectively included newly diagnosed CD ( n = 76; median age 26.2 years (16.0-74.0); 53% male) and UC ( n = 31; median age 25.5 years (16.7–69); 45% male) patients across three Belgian IBD centres (University Hospitals Brussels, Ghent and Leuven). New diagnosis was defined as within 3 months after diagnosis, naïve for biologicals and immunosuppressives, and no previous IBD-related surgery. A panel of 91 inflammatory proteins (OLINK) was quantified in the serum sample taken at diagnosis, and of age- and gender-matched healthy controls ( n = 80, ± 3.6 years). Wilcoxon rank-sum and t-tests were used as appropriate, and multiple testing correction applied (Benjamini–Hochberg method, R 3.4.2). An adjusted p -value of <0.05 was considered significant. Results: Comparison of protein levels in CD patients with matched controls identified 44 significantly different proteins, with OSM (fold change (FC) = 4.0, p = 1.7E−12) and IL-6 (FC = 3.7, p = 3.9E−12) as the most dysregulated proteins. When comparing UC with controls, 39 significantly different proteins were found, 29 of which were also different in CD, incl. IL-6 and OSM (ranked 9th and 10th). The most differentially expressed protein in UC was CXCL1 (FC = 1.7, p = 4.5E−07). We then stratified CD and UC into quartiles based on the age at diagnosis (≤21.5, 21.5–25.5, 25.5–33.5 and >33.5 years for CD; ≤20.6, 20.6–26.0, 26.0–33.7 and >33.7 years for UC), and compared each subgroup with its matched control group. A comparable number of differentially expressed proteins was observed for quartiles 1 to 3 in CD ( n = 25–30 proteins), of which 12 overlapped, incl. OSM and IL-6. Only one protein, FGF-19, was dysregulated in the oldest CD group. For UC patients, quartiles 1 and 2 showed comparable results (13 and 8 different proteins, overlap of 7), while no differences were observed for the two oldest UC groups. Conclusions: We identified panels of inflammatory markers defining newly diagnosed CD and UC, with some common for both (OSM, IL-6), while others appear to be specific for either CD or UC. We found a decreased inflammatory burden with increasing age, providing further evidence for the less severe clinical symptoms in late-onset compared with early-onset IBD.